2002
DOI: 10.1007/s00268-002-6506-2
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of Axillary Dissection in Elderly Women with Early Breast Cancer

Abstract: The need for axillary dissection for staging and treating early breast cancer has been questioned recently. Can a patient forego axillary dissection, with its associated costs, risks, and morbidity, if it does not affect survival? The study attempted to find a subset of patients with early breast cancer in whom disease-free survival was independent of axillary lymph node status. If survival does not depend on lymph node status, axillary dissection could be omitted in the care of these patients. This study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In older women with no palpable lymph nodes, forgoing lymph node dissection in early BC has almost no effect on OS, as shown by the low frequency of recurrence in the axillary lymph nodes [ 41 42 43 44 ]. Contrastingly, axillary lymph node dissection is recommended for patients with clinically positive nodes.…”
Section: Therapymentioning
confidence: 99%
“…In older women with no palpable lymph nodes, forgoing lymph node dissection in early BC has almost no effect on OS, as shown by the low frequency of recurrence in the axillary lymph nodes [ 41 42 43 44 ]. Contrastingly, axillary lymph node dissection is recommended for patients with clinically positive nodes.…”
Section: Therapymentioning
confidence: 99%
“…Newlin et al reported similar findings in 378 patients over the age of 70 years, who had axillary dissection and concluded that the presence of lymph node metastasis did not appear to affect disease free survival rates significantly in elderly patients. 41 Recently, a randomised controlled trial comparing primary surgery with axillary clearance and primary surgery without axillary clearance in women aged 60 years and over (n 5 437; median age 74) reported similar disease free survival (DFS) and overall survival (OS) at a median follow-up of 6.6 years (6-year DFS, 67% v 66%; hazard ratio [HR]: 1.06; 95% CI, 0.79-1.42; p 5 0.69) and OS (6-year OS, 75% v 73%; HR: 1.05; 95% CI, 0.76-1.46; p 5 .77). All patients had clinically node negative disease and received adjuvant tamoxifen for 5 years.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Several studies have reported lower use of ALND and postoperative radiotherapy in the elderly patient (Voogd et al, 1994;Guadagnoli et al, 1998a;Hebert-Croteau et al, 1999;Edge et al, 2002;Giordano et al, 2005). The benefit of ALND for elderly patients has been seriously questioned in the literature (Wazer et al, 1994;Newlin et al, 2002;Martelli et al, 2003) and surgeons may be reluctant to perform an additional ALND (following BCS or SNB) in elderly patients as they frequently suffer from comorbidity. Over the years 2001 -2002, in our study 50% of the patients who did not have an ALND had a tumour positive SNB; most of these patients were over 50 years of age.…”
Section: As Reference)mentioning
confidence: 99%